Sosialisasi “Golden Age” Di Tk Dharma Wanita Bungi - Ode Yahyu Herliany Yusuf; Siana; Feni Aprianti; Meutia Septiani; Sukarni; Helmanidar; Hasriana (CV. Multi Kreasi Media, 2022)
The purpose of community service activities is to provide information to parents regarding the golden age development period in children. At the time of the Golden Age (Golden Age) is the best period in child development, this period is between the ages of 0-6 years where at this time the brain is experiencing rapid development, so that this period is a great opportunity for parents to shape their children into individuals. who are not only healthy and smart, but also moral and have good social skills.